ASYMMETRIC CAUSAL LINKAGES BETWEEN LIQUIDITY AND PROFITABILITY FOR MENA ISLAMIC BANKS - Khoutem Ben Jedidia; Ines Ben Salah (Bank Indonesia, 2022)
This paper investigates the impact of liquidity on Islamic bank profitability. We examine the existence of asymmetric causal linkages or structural shifts in the profitability-liquidity nexus for a sample of 34 Islamic banks in the Middle East and North Africa (MENA) countries over the period 2005-2017 using the Panel Threshold Regression and controlling for the bank-specific and macroeconomic variables. Empirical evidence highlights a non-linear relationship between liquidity and Islamic bank profitability. Indeed, there is a significant negative relationship between liquidity and profitability if the ratio of loan/total assets does not exceed the threshold. Contrariwise, liquidity positively affects profitability. Furthermore, the empirical evidence shows that bank size is adversely related to banks’ profitability given the economies of scale issues of Islamic banks. The CAR impact is well emphasized above and below the threshold. We highlight that Islamic banks face a trade-off between liquidity and profitability. They are recommended to strengthen the liquidity risk management instruments to improve their profitability notably within a framework of Basel III liquidity requirements to maintain adequate high-quality liquid assets.